Metacognitive processes in the self-regulation of performance in elite endurance runners - Brick, N.; MacIntyre, T.; Campbell, M. (Psychology of Sport and Exercise, 2015)
Objective: This study sought to investigate the dynamics of attentional focus and cognitive control during endurance activity from a metacognitive perspective. The study also intended to examine the situational factors which may influence cognitive strategy use by elite endurance runners. Design: Semi-structured qualitative interviews were utilised. Method: Ten elite-level endurance runners were interviewed to explore retrospectively their attentional focus and cognitive strategy use during endurance running. Results: The findings revealed that metacognitive strategies such as planning, monitoring, reviewing and evaluating, and metacognitive experiences were fundamental to cognitive control and cognitive strategy use in elite endurance runners. The findings also added to the array of active self-regulatory strategies previously reported in the literature. Conclusions: These results suggest that metacognitive processes are central to effective cognitive control in elite endurance athletes during running. The findings allowed for the development of an integrative metacognitive framework, which incorporates dimensions of attentional focus. This model may better represent the processes which underpin cognitive control and determine cognitive strategy use in elite athletes during endurance running.